Alice Comes to Law School: The Internet as a Teaching Tool - Bernadette Richards (Legal Education Review)
This edition of Legal Education Review is sure to provide pieces of interest to all readers. The articles range from those which offer insights into the training of legal skills in the law curriculum, to those which discuss innovative ways of engaging students, and all provide thought-provoking commentary about legal education. The Teaching Notes section of Legal Education Review offers the opportunity to read about others’ experiences as law teachers and the trialling of teaching strategies. These might provoke thoughts about your own teaching and learning practices. This Legal Education Review has a new editorial team. I would like to welcome Professor Paul Moyle from Edith Cowan University, Associate Professor Nan Sueffert from Waikato University and Allan Chay from Queensland University of Technology. The continuing support offered by Jeffrey Barnes of La Trobe University is greatly valued. Terry Hutchinson of Queensland University of Technology has also taken a leading role in making this edition come to life. Many thanks go to Angus Young, who administers the Review, and to Sian Jones who worked on editing the contributions. Additionally, the journal acknowledges the important role that our referees play in ensuring the quality of our publication. The Review sincerely appreciates the time and expertise offered by these eminent academics. Legal Education Review thanks the Australasian Law Teachers’ Association and Thomson Legal and Regulatory for its continuing support of the journal. Thomson is a major sponsor of the Legal Education Review. Next year Legal Education Review is moving to one edition each year. Submissions of articles and teaching notes are sought by 30 June 2005 for consideration for inclusion in the 2005 edition. If you wish the Review style guide to be sent to you, please e-mail ler@uts.edu.au. Submissions can also be mailed to ler@law.uts.edu.au. Please direct any inquiries to Lyndal Taylor on lyndal.taylor@uts.edu.au.